Design and Lifting Analysis of Four-Legged Jacket-Type Offshore Platform Structure in the Java Sea - Jansen Benjamin, Steven
Multiple considerations are needed in the process of designing an offshore platform to be used in exploration and exploitation of non-renewable oil & gas resources. The structure is designed as is to be able to avoid collapse and various types of failure when introduced with various loads related to environmental conditions of offshore areas over its design lifetime. Analyses are conducted in the design process to ensure that the structure conforms to the criteria from international standards. This work introduces a design process of a four-legged jacket type offshore platform located in Java Sea, Indonesia. Modeling processes are used to make complicated calculations easier and more precise. The work uses SACS version 5.6 software in its modeling processes. Output parameters from the modeling process are checked according to API RP-2A standard, using Working Stress Design (WSD). Iteration calculations are performed when applicable as a way of optimalization of parameters. Calculation processes are explained thoroughly, complete with general principles of related topics such as offshore platform types and principles behind the numerous calculation processes. Tables and figures are generated when applicable, as to simplify data checking and visualizations. Data acquisition comes from many sources that are all listed in the bibliography at the end of the work. The results of this work is a model design of the structure that conforms to the need of the structure and the standards. The structure meets many criteria of in-place analysis, seismic forcing analysis and fatigue effects analysis on the structure. Installation analysis and results are also provided, complete with lifting configurations of the structure as well as the design of lifting components to support installation of the structure in a safe manner.